KONSEP DAN INDIKATOR DAYA TAMPUNG SOSIAL - Faturochman Faturochman; Ambar Widaningrum (Populasi, 1993)
Even though the definition on social environment carrying capacity has been stated in the Act of The Republic of Indonesia number 10 of 1992, the concept should, however, be developed further, particularly in developing a more 'applicable' social carrying capacity indicators. Ideally, the development of the concepts and indicators of the social carrying capacity is able to formulate the limits of human and group's capabilities in creating social harmony. For this reason, the social carrying capacity is supposed to be looked uponthrough various related aspects all at once. By relating these aspects together, some possible prediction on various conditions of social environment carrying capacity could be carried out.